Application of Fluid Balance Monitoring with Hypervolemia Problems in Chronic Kidney Disease (CKD) Patients in the Rosella Ward of Kardinah Regional General Hospital (RSUD) in Tegal City - Adawiyah, Zulfa Robi’atul; Fadila, Erida; Syaripudin, Ahmad (INDOGENIUS, 2025)
Background & Objective: Chronic Kidney Disease (CKD) is a progressive and irreversible decline in kidney function that causes the body to be unable to maintain metabolism and fluid and electrolyte balance, which can trigger hypervolemia. This study aims to investigate the application of fluid balance monitoring in Chronic Kidney Disease (CKD) patients with hypervolemia. Method: A descriptive method was used, incorporating case study results.  Result: Fluid balance monitoring was conducted over three days in CKD patients with hypervolemia. The results indicated that the hypervolemia issue remained unresolved, as evidenced by persistent edema in the lower extremities, unchanged urine output, and fluid balance monitoring results showing intake of 1,076 cc, output of 592 cc, and a fluid balance of +484 cc. Conclusion: Fluid balance monitoring is important in managing hypervolemia in patients with Chronic Kidney Disease (CKD), but it requires time and further approaches to achieve nursing care objectives.